Students’ Perceptions of Mathematics Learning Based on Their Brain Domination Group - Mumtazah, Nadia Wardah; Dahlan, Jarnawi Afgani; Mulyaning A., Endang Cahya (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2024)
This research discusses students' perceptions of mathematics learning based on their brain dominance. Descriptive qualitative methods were used with questionnaires and interviews. The research subjects were 26 students who filled out a questionnaire in the form of a brain dominance questionnaire, with details of 6 students who were interviewed in depth. Data analysis was carried out through discourse analysis of the interview results by considering the respondent's environmental context. The results of the research show that there are differences in perception between students who are right and left brain dominant and students who use both equally. Some students have different ease and difficulties in learning mathematics, as well as different views about the benefits of this material in everyday life. Apart from brain dominance, there are several other factors that influence students' perceptions, including the way teachers teach and the learning environment. Knowing students' brain dominance is important, because it can help teachers determine how to teach material appropriately so that it gets a good perception for all students, whether they are right-brain dominant, left-brain dominant, or those who tend to be balanced. In conclusion, students' perceptions of mathematics learning can be different, depending on their brain dominance.